Respuesta :

Answer:

See Explanation

Step-by-step explanation:

The question is incomplete, as the functions are not given.

The general explanation on calculating average rate of change is as follows.

The average rate of change (m) of function f(x) over interval (a,b) is:

[tex]m = \frac{f(b) - f(a)}{b-a}[/tex]

Take for instance:

[tex]f(x) = x^2 + 4x + 4[/tex]

[tex](a,b) = (0,2)[/tex]

The average rate of change over [tex](0,2)[/tex] is:

[tex]m = \frac{f(2) - f(0)}{2-0}[/tex]

[tex]m = \frac{f(2) - f(0)}{2}[/tex]

Calculate f(2) and f(0)

[tex]f(2) = 2^2 + 4*2 + 4 =16[/tex]

[tex]f(0) = 0^2 + 4*0 + 4 =4[/tex]

So, we have:

[tex]m = \frac{f(2) - f(0)}{2}[/tex]

[tex]m = \frac{16 - 4}{2}[/tex]

[tex]m = \frac{12}{2}[/tex]

[tex]m = 8[/tex]

Answer:

Maybe you could show what is trying to be solved.

Step-by-step explanation: